On The Use Of The Cohesive Zone Model In Validating Mixed-Mode Bending Apparatus Design - Syamsudin, Hendri; Suada, M Giri; Adhitama, Muhammad Daffa (Indonesian Journal of Aerospace, 2025)
Understanding the strength of adhesive materials has been increasingly relevant due to their expanding use in many industries. The importance of understanding its mixed-mode behavior also increases since realistic loading cases rarely involve pure mode I and pure mode II loads. The mixed-mode bending (MMB) test, standardized by ASTM D6671, is a particularly intriguing test that could be used to map adhesive strength in a whole range of mixed-mode ratios, only by using a single specimen design. An MMB apparatus design has been developed based on guidelines provided by ASTM D6671 to test aluminum adherends with modifications that conform to local manufacturing capabilities and material availability. This design was then numerically inspected using the Cohesive Zone Model (CZM) and Benzeggagh-Kenane (B-K) model to check its validity and understand its work range. Mesh convergence test, adherend stiffness variation, and adhesive strength variation were conducted in ABAQUS. Results show satisfactory stability and validity of the design to test aluminum adherends.